Digital Contracts and Jurisdiction in Global E-Commerce: Legal Standards, Clause Validity, and Enforcement Across Borders - Supangat, Ajis; Nasution, Emmi Rahmiwita; Sara, Rineke (Legalis : Journal of Law Review, 2024)
The exponential rise of cross-border e-commerce has presented critical legal challenges regarding jurisdiction, applicable law, and enforcement of consumer disputes. This article aims to provide a comparative and doctrinal analysis of how different jurisdictions primarily the European Union, United States, ASEAN, and Indonesia approach these challenges through domestic legislation, regional instruments, and global conventions. The research employs doctrinal comparative legal methods, analyzing legal instruments such as the Brussels I Recast, Rome I and II Regulations, the Hague Conventions (2005 and 2019), and the New York Convention. Key case law including Pammer, Emrek, Schrems, and Nguyen is examined to highlight judicial interpretations. The analysis includes ASEAN’s regional cooperation frameworks and Indonesia’s regulatory evolution. The results show significant divergence in jurisdictional tests (e.g., the EU’s targeting test vs. the US’s contractual autonomy), clause validity standards (clickwrap vs. browsewrap), and enforcement mechanisms. While the EU offers a structured consumer protection regime, the US emphasizes freedom of contract. ASEAN's soft-law frameworks and Indonesia’s domestic regulations show promise but face implementation and enforcement challenges. The Hague Judgments Convention remains underutilized, while arbitration via the New York Convention proves more reliable for cross-border enforcement. The study concludes that despite substantial progress in developing international legal tools, their effectiveness is undermined by fragmented implementation and regulatory divergence. Harmonization efforts must prioritize enforceable assent standards, broader ratification of international conventions, and capacity-building within national systems particularly in emerging economies.